PENGARUH PROFITABILITY TERHADAP MARKET CAPITALIZATION PERBANKAN KONVENSIONAL (2012-2021) - Dhea Prisma Shelawangi; Marlinda Nur Aisyah; Fathur Rozi Farori; Vira Yulita Kurniawati (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to determine whether the profitability ratios can affect the value of market capitalization. So the researchers drew the title